2017
DOI: 10.2174/1871529x17666170703115545
|View full text |Cite
|
Sign up to set email alerts
|

Is Anticoagulation with Novel Oral Anticoagulants an Effective Treatment for Tuberculosis Patients not Achieving a Therapeutic Range with Vitamin K Antagonists? A Systematic Review

Abstract: 1011 titles were identified on PubMed and Google Scholar published from the inception to February 5, 2017, of these 17 studies were included in the qualitative synthesis Conclusion: No published data were found that properly assessed the effect of NOAs administered in combination with anti TB antimicrobials. Further studies are needed to establish the safety of NOAs in this clinical scenario. In the meanwhile, a viable alternative to VKAs, in order to prevent complications of VTE related to TB, may be represen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“… [51] Newer anticoagulants such as dabigatran and rivaroxaban require less monitoring and are said to have fewer drug interactions in those receiving therapy for TB or HIV. [54 , 55] Some studies have shown these agents to be efficacious and cost effective in developed countries. [56] There are a few studies analysing the cost effectiveness of these newer agents in public hospitals in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“… [51] Newer anticoagulants such as dabigatran and rivaroxaban require less monitoring and are said to have fewer drug interactions in those receiving therapy for TB or HIV. [54 , 55] Some studies have shown these agents to be efficacious and cost effective in developed countries. [56] There are a few studies analysing the cost effectiveness of these newer agents in public hospitals in developing countries.…”
Section: Discussionmentioning
confidence: 99%
“…Lind et al 8 "The aPTT does not correlate well with other tests that might be used to monitor parental DTI administration. "…”
Section: How Of Ten Are Parenter Al Anticoag Ul Ants Adminis Tered By...mentioning
confidence: 99%
“…Table 1 summarizes the errors that could be identified from this second search. In total, we identified 12 errors related to use of “parentally” administered “anticoagulants.” 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 Interestingly, the search string ((parenteral) AND (heparin OR anticoagulant OR enoxaparin OR clexane OR DTI OR “thrombin inhibitor” OR anticoagulant OR lepirudin OR argatroban OR bivalirudin)) only identified 2865 items, and so only around twice the number using “parental” instead of “parenteral” ( n = 1479).…”
Section: How Often Are Parenteral Anticoagulants Administered By Pare...mentioning
confidence: 99%
“…DOACs could be an alternative for anticoagulation. However, data on their efficacy and safety in such cases are only a few [ 87 ].…”
Section: Tuberculosis and Vtementioning
confidence: 99%